2020
DOI: 10.1101/2020.12.30.424594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial community dynamics during embryonic development of the little skate (Leucoraja erinacea)

Abstract: Microbial transmission from parent to offspring is hypothesized to be universal in vertebrates. However, evidence for this is limited as many clades remain unexamined. Chondrichthyes, as one of the earliest–branching vertebrate lineages, provide an opportunity to investigate the phylogenetic breadth of this hypothesis. To assess the potential for bacterial transmission in an oviparous chondrichthyan, we used 16S rRNA amplicon sequencing to characterize the microbial communities associated with the skin, gill, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 100 publications
(173 reference statements)
2
0
0
Order By: Relevance
“…An experiment on a human skin modelled showed that mixed microbiome communities had a greater positive effect on the skin function, including the mediation of the epidermal layer thickness, reduction in the number of actively proliferating cells, and increased filaggrin expression [59], suggesting that there is a two-way interaction between the microbes and host metabolic processes. The epidermal microbiome of embryonic skates showed a dramatic change at the time of dermal denticle hardening, going from similar to other body parts prior to denticle formation to unique post denticle formation [72], supporting our hypothesis that the dermal denticles affect microbiome structure. There was no evidence of dentine, hydrolysate, or collagen degradation in the shark skin microbiome, suggesting that the microbes are not breaking down the dermal denticles, which signifies a lack of negative impact on the sharks, at least in the form of degrading the dermal denticles.…”
Section: Gene Functions Linked To Host Metabolic Processessupporting
confidence: 80%
See 1 more Smart Citation
“…An experiment on a human skin modelled showed that mixed microbiome communities had a greater positive effect on the skin function, including the mediation of the epidermal layer thickness, reduction in the number of actively proliferating cells, and increased filaggrin expression [59], suggesting that there is a two-way interaction between the microbes and host metabolic processes. The epidermal microbiome of embryonic skates showed a dramatic change at the time of dermal denticle hardening, going from similar to other body parts prior to denticle formation to unique post denticle formation [72], supporting our hypothesis that the dermal denticles affect microbiome structure. There was no evidence of dentine, hydrolysate, or collagen degradation in the shark skin microbiome, suggesting that the microbes are not breaking down the dermal denticles, which signifies a lack of negative impact on the sharks, at least in the form of degrading the dermal denticles.…”
Section: Gene Functions Linked To Host Metabolic Processessupporting
confidence: 80%
“…These features are consistent across the microbiome of four shark species [26,28]. The epidermal microbiome of embryonic skates showed a dramatic change at the time of dermal denticle hardening, going from similar across all body parts to a unique microbiome on the epidermis [72], confirming the effect of the dermal denticles in microbiome structure.…”
Section: Leopard Shark Microbiome Exhibits Specificity and Flexibilitysupporting
confidence: 66%